Central Research Institute for Epidemiology Became a PrizeWinner of the Contest «The Best Implemented Project in the Field of Construction», Organized by the Moscow City Government Pressrelease of August 26, 2022 - article Editorial (Эпидемиология и вакцинопрофилактика)
.